TINJAUAN LOCA ANTARA ATS REPORTING OFFICE DAN AIRLINES TERHADAP EFEKTIVITAS PELAYANAN NAVIGASI UDARA DI PERUM LPPNPI CABANG PATTIMURA AMBON - Vania Kylaemery; Ade Irfansyah; Paramita Dwi Nastiti (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
This final project describes the obstacles faced by the author regarding the provision of Flight Information Service in the ATS Reporting Office (ARO) Ambon unit. The problem with the Ambon ATS Reporting Office (ARO) unit is the delay of the Airlines in sending the Flight Plan that is not in accordance with the LOCA between the ATS Reporting Office (ARO) and the Airlines on the Flight Plan delivery, which is a minimum of 24 hours before departure and a maximum of 120 minutes before departure. time estimate off block time (EOBT). The emergence of these obstacles was due to the lack of knowledge of the Airlines regarding the Letter of Coordination Agreement (LOCA). In addition, the lack of coordination from the Airlines unit regarding the delay in sending the Flight Plan also hampered the process of providing navigation services. The results of the data obtained during the author conducting research at the same time as the author conducting On the Job Training, namely on November 02, 2020 to March 17, 2021 at Perum LPPNPI, Pattimura Ambon Branch, are expected to provide input and suggestions so that existing problems can be resolved and service delivery can be achieved. running optimally. These obstacles can be resolved by reviewing the Letter of Coordination Agreement (LOCA) so as to create an effective and efficient service delivery.